Study of tritium desorption by energetic ion bombardment from tungsten material. (17th December 2015) - Kato, Shuichi; Ito, Atsushi M.; Takayama, Arimichi; Sasao, Mamiko; Wada, Motoi; Nakamura, Hiroaki
Abstract: To solve the problem of tritium retention in a nuclear fusion reactor, the removal of hydrogen isotopes retained in a tungsten material by exposure to the other hydrogen isotope plasma was investigated. We proposed the balance equation between the absorption and desorption of the hydrogen isotope atoms in the tungsten material. Absorption ratio and desorption yield were calculated by binary collision approximation simulation. Simulation results showed that desorption yield was proportional to the concentration of the retained hydrogen isotope. Therefore, the decrease in the retained hydrogen isotope atoms by hydrogen plasma irradiation can be regarded as approximately exponential decay. The decay rate in the case that retained deuterium atoms are removed by light hydrogen irradiation was two thirds of the decay rate in the case that retained tritium atoms are removed by deuterium irradiation.